Nutrient Use Efficiency Indices in Maize Hybrid as A Function of Various Rates of NPK in Mid Hills of Nepal - Nabin Rawal; Keshab Raj Pande; Renuka Shrestha; Shree Prasad Vista (Turkish Journal of Agriculture: Food Science and Technology)
Field experiments were conducted to evaluate yield and nutrient use efficiency in maize in response to various rates of nitrogen (N), phosphorus (P) and potassium (K) in silty clay loam soil of Khumaltar, Nepal during 2019 and 2020. Three factorial randomized complete block designs with 27 treatment combinations were used in experiments, which were repeated three times. Three factors were N levels (150, 180, 210 N kg ha-1), P levels (40, 60, 80 P2O5 kg ha-1), and K levels (40, 60, 80 K2O kg ha-1). The results recommend to revise fertilizer dose since N210 kg ha-1 and K2O 80 kg/ha were optimum for increased maize production with grain yields of 10.95 t ha-1 and 10.54 t ha-1, respectively. Partial factor productivity, partial nutrient budget, internal efficiency, physiological efﬁciency, recovery efficiency, and agronomic efﬁciency of NPK for hybrid maize were mostly influenced by nutrient levels. Application of higher rate of P and K fertilizer improved maize N efficiencies, and case was valid for P and K efficiencies. Maize was more responsive to N and K fertilizer and lower rate of P application limited efficient use of applied N and K. To increase overall NUE, we recommend to revise dose of fertilizer for hybrid maize under mid hill condition of Nepal.